An In Situ Coupling Strategy toward Porous Carbon Liquid with Permanent Porosity. Issue 10 (27th January 2021) - Li, Peipei; Wang, Dechao; Zhang, Lu; Liu, Chao; Wu, Fei; Wang, Yongkun; Wang, Zheng; Zhao, Zhenhuan; Wu, Weiwei; Liang, Yanping; Li, Zhimin; Wang, Weidong; et al.
Abstract: An in situ coupling approach is used to fabricate the porous carbon liquid with permanent porosity by directly dispersing hollow carbon nanospheres in polymerized ionic liquids. It is a kind of homogenous and stable type III porous liquid at room temperature. Because of the well‐preserved permanent porosity, this unique porous carbon liquid is capable of absorbing the largest quantity of carbon dioxide than the reference PILs and solid carbon liquid, thus, can function as a promising candidate for application in gas storage. More importantly, this approach not only provides an easy method to tune the properties of those specific porous liquids, but also is suitable for fabricating other porous liquid based on varied porous structures (e.g., porous carbon nitride, porous boron nitride, and polymer with intrinsic microporosity), thus paving a viable path for the rational design and synthesis of novel porous liquids with functional properties for specific applications. Abstract : Porous carbon liquid with permanent porosity is fabricated by dispersing hollow carbon nanospheres in polymerized ionic liquids through the cation‐π interaction via an in situ coupling strategy. Thus, possibilities for the rational design and preparation of novel porous liquids for specific applications are opening up.